Adapt to Translate – Adaptive Clinical Trials and Biomedical Innovation - Daria Jadreškić (European Journal of Analytic Philosophy, 2021)
The article presents the advantages and limitations of adaptive clinical trials for assessing the effectiveness of medical interventions and specifies the conditions that contributed to their development and implementation in clinical practice. I advance two arguments by discussing different cases of adaptive trials. The normative argument is that responsible adaptation should be taken seriously as a new way of doing clinical research insofar as a valid justification, sufficient understanding, and adequate operational conditions are provided. The second argument is historical. The development of adaptive trials can be related to lessons learned from research in cases of urgency and to the decades-long efforts to end the productivity crisis of pharmaceutical research, which led to the emergence of translational, personalized, and, recently, precision medicine movements.